Analisis Penyebab Error Ca559 pada Excavator Komatsu Pc200-8m0 Melalui Evaluasi Kebocoran Injector Sistem Common Rail - Cipta, Denny Hendra; Ramli, Ismail; Halman, Halman; Anggini, Canda Putri; Viddy, Arkas (Syntax Corporation, 2025)
Error CA559 on the Komatsu PC200-8M0 excavator is an indication of a drop in pressure in the common rail fuel system that can cause combustion failures, decreased engine performance, and increased emissions. This study aims to analyze the main causes of CA559 errors through a thorough evaluation of the condition of the fuel system, especially the injector components. The research methods include field observation, operator interviews, visual examinations, cut-out tests, as well as return flow measurements of injectors and supply pumps based on manufacturer's standards. The measurement results showed that the number 6 cylinder injector had a return flow value of 500 cc/min, far exceeding the standard limit of 180 cc/min, indicating a significant internal leakage. This condition causes unstable rail pressure, incomplete combustion, engine vibration, and the appearance of black smoke. Evaluation of other components such as inlet pressure, pressure limiter, and return supply pump shows that the results are still within normal limits. Thus, it can be concluded that the main cause of the CA559 error is an internal leak in injector number 6. Replacement of injectors and improved fuel quality control are recommended to prevent the recurrence of similar disturbances.